2021
DOI: 10.3390/ijms22126514
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Vessels Fuel the Fire in Glioblastoma

Abstract: Glioblastoma, a subset of aggressive brain tumors, deploy several means to increase blood vessel supply dedicated to the tumor mass. This includes typical program borrowed from embryonic development, such as vasculogenesis and sprouting angiogenesis, as well as unconventional processes, including co-option, vascular mimicry, and transdifferentiation, in which tumor cells are pro-actively engaged. However, these neo-generated vascular networks are morphologically and functionally abnormal, suggesting that the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 178 publications
(218 reference statements)
1
46
0
Order By: Relevance
“…Glioblastoma multiforme (GBM) is a very aggressive brain tumor [ 1 ] characterized by high inter- and intratumor heterogeneity [ 2 ] with high local invasiveness [ 3 ], extensive necrosis [ 4 ], and high vascularity [ 5 ]. Current standard treatments for this neoplasm include surgical resection combined with radiotherapy (RT) and chemotherapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is a very aggressive brain tumor [ 1 ] characterized by high inter- and intratumor heterogeneity [ 2 ] with high local invasiveness [ 3 ], extensive necrosis [ 4 ], and high vascularity [ 5 ]. Current standard treatments for this neoplasm include surgical resection combined with radiotherapy (RT) and chemotherapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for SLUG, combined FISH-immunofluorescence showed that TAL1 is present in few GBM EGFR-amplified tumoral cells. Considering that TAL1 is involved in endothelial differentiation during development and controls active angiogenesis in later stages, it is tempting to speculate that these TAL1 + GBM cells are endothelial-like cells, which have been previously described [ 81 , 82 ] and would result from a trans-differentiation of GBM cells [ 70 , 71 ]. Additional work is needed to establish the identity of these TAL1 + GBM cells, their contribution to GBM progression, and if they potentially participate in neovascularization processes.…”
Section: Discussionmentioning
confidence: 99%
“…This dual tumoral vs. non tumoral expression of SLUG was also observed at the RNA level, using one recent glioblastoma RNA seq database ( Figure S5E ) [ 48 ]. Due to technical limitations, we did not fully demonstrate that these SLUG + tumoral cells also co-expressed smooth muscle markers and adopted a pericyte-like phenotype as a result of a GBM-vascular trans-differentiation process [ 70 , 71 , 72 ]. More work using new multiplexing approaches would be necessary to address this issue and assess the contribution of SLUG + GBM cells to GBM progression and, potentially, to neovascularization mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the third place, the identification of different subsets of GSCs represents another controversial point. The GSCs are characterized by sustained self-renewal, persistent proliferation, tumor initiation, frequency within a GBM tumor, marker expression, ability to generate progeny of multiple lineages, and chemo/radio resistance [ 169 , 179 , 180 ]. There is no consensus for the surface markers used for identifying the GSCs, which are constantly updated [ 181 ].…”
Section: Glioma Stem Cellsmentioning
confidence: 99%